Pictorial key to adult female Culicoides Latreille, 1809 (Diptera: Ceratopogonidae) from the Northern Territory, Western Australia and South Australia. Issue 1 (17th July 2014) - Bellis, Glenn A; Halling, Luke; Anderson, Stacey J
Abstract An illustrated key to aid in separating adult females of the 64 species of Culicoides reported from the Northern Territory, Western Australia and South Australia, and some important livestock pest species not present in these regions is presented. The key uses characters visible under a stereomicroscope and does not attempt to distinguish those species that are separable only on characters visible on slide‐mounted specimens. C. asiana Bellis is proposed as a replacement name for C. asiatica Bellis.